Modelling of interconnects including coaxial cables and multiconductor lines - Teo, Yu Xian (2013)
In recent years, electromagnetic compatibility (EMC) problems associated with high frequency and high speed interconnects are becoming of increasing concern. Coaxial cables are a popular form of interconnect. In this thesis, the crosstalk coupling between two parallel coaxial cables in free space and above a ground plane is investigated. The degree of coupling is usually formulated analytically in the frequency domain. In this thesis, a method for time domain simulation is proposed using the TLM technique. Results are compared with frequency domain solutions and experimental results. Also; the standard model has been improved by including the skin depth effect in the coaxial cable braid.